Flower Abortion and Fruit Yield Responses of Two Varieties of Chilli Pepper (Capsicum frutescens L.) to Different Planting Dates and Plant Densities - M. T. Mends-Cole; B. K. Banful; P. K. Tandoh (Archives of Current Research International, 2019)
Field and laboratory experiments were carried out between April 2014 and March 2015 to evaluate the effects of planting date and density on flower abortion and fruit yield of two chilli varieties. The field trial was laid out in 2x3x3 factorial experiment in a Randomized Complete Block Design (RCBD) with 3 replications. The factors studied included two chilli varieties (Shito Adope and Legon-18); three planting dates (May 12, 2014; June 13, 2014; and September 29, 2014); and plant spacing at three levels (60 cm x 30 cm; 70 cm x 30 cm; 80 cm x 30 cm). The field study was conducted at the Crops Research Institute-Kwadaso Station, Kumasi, Ghana. Growth and yield were evaluated during the study period. Legon-18 exhibited higher performance than Shito Adope for parameters such as plant height, branch numbers, canopy width and fruit yield, number. In contrast, Shito Adope took fewer days to attain 50% flowering and fruit set. Shito Adope also recorded higher flower drops. Dates of sowing significantly affected growth and seed quality parameters with the May and June recording taller plants, more branches, wider canopies, and higher fruit yield. Early flowering and fruit set were attained during the same period; while flower drops were more prevalent during the first and third dates of sowing. Planting density showed no significant effect on all parameters studied except plant height, with the widest spacing (80 x 30) recording the tallest plant heights. The results indicates that for periods with extremely high temperatures should be avoided as they tend to increase the rate of flower drops.